ANALISIS PENGEMBANGAN KOMPETENSI PEGAWAI DI BAGIAN TATA PEMERINTAHAN SEKRETARIAT DAERAH KABUPATEN LAMPUNG SELATAN - Cipto Handoko; Faturahman Mahista (e-JKPP, 2023)
This research is entitled Analysis of Employee Competency Development in the Governance Section of the Regional Secretariat of South Lampung Regency, which aims to find out and analyze employee competency development and what factors hinder the development of employee competencies in the Governance Section of the Regional Secretariat of South Lampung Regency. The research method used is the descriptive qualitative method. The sampling technique used was a purposive sampling technique. The main instrument is a researcher who is supported by the results of interviews. The research informants consisted of 10 employees of the Regional Secretariat of South Lampung Regency and the Secretary of the Staffing and Human Resources Development Agency of South Lampung Regency. The results showed that the implementation of employee competency development through formal education and training was not optimal due to a lack of budget and limited opportunities for employee competency development. Based on the results of the study, the researchers provide implications for the South Lampung Regency Government that there is a need for education and training to improve employee competence in the Governance Section of the Regional Secretariat of South Lampung Regency by providing study assignments and including employees in structural training and technical training. Then, additional budgets and quotas for attending education and training must be added so that there are more opportunities for employees in the Governance Section of the Regional Secretariat of South Lampung Regency to develop competencies.